2007
DOI: 10.4314/mmj.v19i1.10929
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and bacterial colonization of burn injuries in Blantyre

Abstract: Forty-nine patients from the Burns Unit at the QECH had swabs taken from various sites in order to determine the bacterial profile and antibiotic susceptibilities in burn wounds colonized by bacteria. The mean age was 16 years (range 1-70 years); 27 (55 %) of the study population were female and 22 (45%) were male. Twenty-four (49%) patients were epileptic. Open fire (41%) was the most common cause of burn injuries among epileptics while hot water burns (29%) were commonest among non-epileptics. Burn injury an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 17 publications
1
29
1
Order By: Relevance
“…59 Other reasons for this finding may be due to delay excision which increase the reservoir of bacteria made up by the collective burn wound surfaces of patients in a burn management, which is mentioned by Mayhall, C.G. 60 However, in our study the proportion of infection decreased with increasing TBSA burnt when more than 40% which accounted 35.4% (Table 4).…”
contrasting
confidence: 51%
“…59 Other reasons for this finding may be due to delay excision which increase the reservoir of bacteria made up by the collective burn wound surfaces of patients in a burn management, which is mentioned by Mayhall, C.G. 60 However, in our study the proportion of infection decreased with increasing TBSA burnt when more than 40% which accounted 35.4% (Table 4).…”
contrasting
confidence: 51%
“…7,8 In present study, most common age group involved was 31-40 years (28.04%) with female (56.09%) preponderance. In agreement to present study Mundhada et al reported most common age group as 20-30 years with females (54%) preponderance.…”
Section: Discussionmentioning
confidence: 49%
“…Such initial colonisation always carries the potential to cause overt burn wound infection and subsequent invasion of the Bloodstream. Therefore, identifying the burn wound isolates and testing their susceptibility to antimicrobial agents are important in the management of the burn wound sepsis (13). Female preponderance in burn patients in India may be due to their confinement to the Home, their loose outfits and unfortunate practice of bride-burning for dowry .We found that to start with, the burn wounds were mostly sterile as surface microbial are destroyed by heat.…”
Section: Discussionmentioning
confidence: 90%
“…Colonisation may occur initially from normal resident flora in skin and throat, like staphylococci andstreptococci; later organisms from the gastrointestinal tract, likeE. coli, Klebsiella, Proteus, etc., may also become involved (12,13). In addition, infection may also be transmitted by fomites or the hands of personnel (12).…”
Section: Discussionmentioning
confidence: 99%